Analysis of the Influence of Policy, Commitment and Financial Factors on Value Engineering – Based Investment Cost in Green Data Center Projects - Febriyani, Ekarismah; Suroso, Agus Suroso (Universitas Negeri Yogyakarta, 2025)
The Global Warming phenomenon caused by the greenhouse gas effect that raises the need for sustainable energy management, especially in the Data Center Industry which is known to contribute 2% of emissions, because 35% of energy use is for cooling. This study aims to analyze the influence of government policy factors, agency commitments, and finances on investment costs based on Value Engineering in the Green Data Center project, find the dominant factor among the factors assessed, calculate Value engineering on the investment costs of the Green Data Center to calculate the life cycle Cost Analysis. The research method uses a combination of quantitative & Qualitative methods with data collection techniques through Primary Data and Secondary Data, Secondary data is obtained based on project information such as Bill of Quantity, Technical Specifications and project reports. Primary data is obtained through questionnaires to stakeholders of the Data Center project, as well as multiple linear regression analysis to test the relationship between variables. The results of the study indicate that the factors assessed have a significant effect on the investment costs of environmentally friendly projects. The application of a renewable energy system through the Value Engineering stages has proven effective in optimizing investment costs through identifying the use of an energy-efficient Liquid cooling cooling system for medium-scale Data Centers which results in savings of around 15.34% and increases Energy Use Efficiency (PUE). While Life Cycle Cost Analysis (LCCA) shows long-term operational savings and a return on investment that is considered fast > than 3 years, the Green Data Center project is feasible to implement. The most dominant factor is the financial support aspect, followed by government policy and agency commitment. This study reinforces the importance of implementing environmentally friendly concepts to support energy efficiency in supporting climate change control and providing long-term economic benefits.